Design an Eddy Current Dynamometer with 0.85 mm Copper Wire and 560 Core Coil Windings - Prasetyo, Rio Dwi; Adhes Gamayel; Mohamad Zaenudin (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The eddy current dynamometer is a torque test measuring instrument calculated from the loading of an engine that rotates on its shaft to stop a rate from engine rotation and produce the engine loading power. The eddy current dynamometer is a torque test measuring instrument calculated from the loading of an engine that rotates on its shaft to stop a rate from engine rotation and produce the engine loading power. The braking system is one of the most important things in an engine, to stop the engine from moving braking is needed. This study aims to calculate the torque of the eddy current dynamometer. With a copper wire diameter of 0.85 mm and 560 windings of the core coil. Torque results show an increase in each variation in current and rotation. The torque power reaches its maximum point at 3000 RPM revolutions at 15V voltage at 25.4A amperes, namely 2.15 Nm. The number of windings on the wire coil is proportional to the magnitude of the solenoid value. The calculation of the maximum value induction at the center of the magnetic force pole core is obtained from the wire diameter of 0.85mm and 560 windings of the core coil at a voltage of 15V in amperes of 25.4A at a roller rotation of 3000 RPM of 254-4 Tesla or Wb/m2. And from both ends of the polar core solenoids, the result of magnetic strength is smaller than the magnetic induction center of the polar core, which is 127-4 Tesla or Wb/m2.